Online private tutor finder system - Heng, Jie You (2023)
This project is to build an online private tutor finder system for academic purposes. The system will be built is a native mobile application which includes the development of the frontend and backend, with incorporation of external APIs to build a whole functioning application. The application will need to support three party which are students, parents, and tutors. At first, through researching in the existing market of the relevant application, there are five problem that has been found which are most of the application does not support the learning of students with learning disordered, lack of time management system, lack of location approximation, lack of mini game section, and lack of a proper payment system. The research is conducted through reading journal articles, checking on the statistics of the students with special needs through Malaysian Government Website, and personally testing and review the existing application in the market. Then later in the project, the method of development is written as a proposal to building the application from scratch, where building the frontend design of the application then incorporate it with backend programming later in the project, which allow get and fetch of the data through database, and a proper payment system that is proposed to be added into the application.